2016
DOI: 10.1093/eurheartj/ehw333
|View full text |Cite
|
Sign up to set email alerts
|

Iron-regulatory proteins secure iron availability in cardiomyocytes to prevent heart failure

Abstract: ID in cardiomyocytes impairs mitochondrial respiration and adaptation to acute and chronic increases in workload. Iron supplementation restores cardiac energy reserve and function in iron-deficient hearts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
144
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(162 citation statements)
references
References 29 publications
5
144
0
4
Order By: Relevance
“…Importantly, further therapeutic options that could lead to functional improvement and reverse remodelling in CRT patients with incomplete reverse remodelling are limited, as patients by selection are on maximal tolerable doses of neurohormonal blockers. 5,18 Nevertheless, these artificially induced iron deficiency cell-based and animal models exhibit extreme iron depletion, limiting the clinical relevance towards real-world patients. Indeed, most therapies that improve outcome such as angiotensin-converting enzyme inhibitor, angiotensin receptor blocker, beta-blockers, mineralocorticoid receptor antagonists, and CRT all induce reverse remodelling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, further therapeutic options that could lead to functional improvement and reverse remodelling in CRT patients with incomplete reverse remodelling are limited, as patients by selection are on maximal tolerable doses of neurohormonal blockers. 5,18 Nevertheless, these artificially induced iron deficiency cell-based and animal models exhibit extreme iron depletion, limiting the clinical relevance towards real-world patients. Indeed, most therapies that improve outcome such as angiotensin-converting enzyme inhibitor, angiotensin receptor blocker, beta-blockers, mineralocorticoid receptor antagonists, and CRT all induce reverse remodelling.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, the presence of iron deficiency at the time of CRT implant is associated with diminished cardiac reverse remodelling and limited functional improvement. 5,18 The effect of intravenous ferric carboxymaltose on reverse remodelling following cardiac resynchronization therapy (IRON-CRT) trial was specifically designed to answer two important questions: (i) if treatment with ferric carboxymaltose induces incremental reverse remodelling in CRT patients with iron deficiency and a persistently reduced left ventricular ejection fraction and (ii) if treatment with ferric carboxymaltose is capable of improving cardiac contractility (force-frequency relationship) in vivo. 15 Normally, when heart rate increases, cardiac contractility increases disproportionally, a process termed 'positive force-frequency relationship or Treppe phenomenon'.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a rule, the action of cardioprotectors is not directly connected with hemodynamic effect, but is mediated by optimization of the processes of energy generation and expenditure, correction of respiratory chain function, normalization of balance between the intensity of the processes of free-radical oxidation and antioxidant protection, and direct impact on cardiomyocytes, thus, contributing to cell survival under conditions of hypoxia and ischemia while preventing the formation of myocardial metabolic remodelling (Gunina, 2016;Haddad et al, 2017). Therefore, the normalization of the processes of energy generation in the myocardium represents the direct way to preserve functional state of the myocardium and cell mitochondrial apparatus under physical loads (Ikeda et al, 2015) and those of aerobic character, in the first place (Rana et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…68 Intravenous iron treatment results in considerable improvements in 6MWT and quality of life, and a meta-analysis suggest that it also reduced HF hospitalization. 69 It would be appealing to treat with oral rather than intravenous iron, but bioavailability is low and the large IRONOUT-HF trial showed that oral iron did not improve peak VO2, 6MWT, KCCQ score, or NTproBNP levels.…”
mentioning
confidence: 99%